2005
DOI: 10.1097/01.ju.0000141582.15218.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights Into Prostate Cancer Progression: The Missing Link of Tumor Microenvironment

Abstract: Cancer is not a single cell disease. Aberrant cancer cells and their interactive microenvironment are needed for prostate cancer to progress to androgen independence and distant metastasis. It is highly plausible that newly evolved prostate cancer cell clones dominate cancer metastasis after cell-cell and cell-matrix interaction with the host microenvironment, rather than the selection or expansion of a preexisting prostate cancer cell clone(s). Based on this premise potential molecular targets in the microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
258
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 313 publications
(268 citation statements)
references
References 59 publications
6
258
0
1
Order By: Relevance
“…These findings suggest that the biological impact of NMU expression on tumor formation is highly related to the tumor microenvironment. This is consistent with the evidence that tumor-microenvironment Neuromedin U enhances lung metastasis Y Wu et al interactions affect local cancer growth, invasion and metastasis (Chung et al, 2005). NMU can also induce the release of inflammatory cytokines in T helper-2 (Th2)-type T cells, mast cells or macrophages (Johnson et al, 2004;Moriyama et al, 2005Moriyama et al, , 2006.…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggest that the biological impact of NMU expression on tumor formation is highly related to the tumor microenvironment. This is consistent with the evidence that tumor-microenvironment Neuromedin U enhances lung metastasis Y Wu et al interactions affect local cancer growth, invasion and metastasis (Chung et al, 2005). NMU can also induce the release of inflammatory cytokines in T helper-2 (Th2)-type T cells, mast cells or macrophages (Johnson et al, 2004;Moriyama et al, 2005Moriyama et al, , 2006.…”
Section: Discussionsupporting
confidence: 89%
“…Collagen I is a heterotrimeric, fibrillar protein that is the major structural extracellular protein in most tissues (Chung et al, 2005). Collagen I has been the most extensively examined collagen in aged hosts and the consensus is that ageing confers a progressive decrease in collagen I synthesis at the same time there is an increase in collagen I degradation.…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…The normal prostate has an abundance of stromal components, mainly well-differentiated smooth muscle cells. In prostate tumors, however, fibroblasts surrounding cancer cells are associated not only with the initiation of cancer cells but also with tumor growth and progression to androgen independence (11)(12)(13). Olumi et al demonstrated stroma-induced malignant transformation, indicating that fibroblasts surrounding epithelia play an important role in PCa development (14).…”
Section: Introductionmentioning
confidence: 99%